Salinidad en suelos cultivados con melocotonero en el Valle del Guadalquivir - Fernandez Escobar, R.=700 1 Perez La Torre, F; Parra, M.A.
(Es, En)
ilus., 12 ref.
Keywords: SALINIDAD; SUELO SALINO; CLORUROS; BORO; SODIO; PRUNUS PERSICA; ESPAÑA; DURAZNO